Primary pediatric endonasal dacryocystorhinostomy--a review of 58 procedures - Komínek, Pavel; Cervenka, Stanislav; Matousek, Petr; Pniak, Tomás; Zeleník, Karol (International journal of pediatric otorhinolaryngology, 2010)
OBJECTIVES: The objectives of this study are to report the outcomes of pediatric patients with lacrimal system obstruction who underwent primary endoscopic dacryocystorhinostomy (EDCR). STUDY DESIGN: The authors conducted a retrospective noncomparative case series. METHODS: The operative and postoperative data have been collected in 58 children aged between 3 months and 13 years (mean 4.1 years). The total of 58 primary EDCRs has been performed by two surgeons using a standardized surgical technique. The EDCRs were performed 52 times on one eye, 6 times on both eyes (3 times simultaneously, 3 times at the separate sitting with an interval of 4-6 months). The follow-up evaluations include taking history, clinical examinations including a fluorescein disappearance test. RESULTS: The follow-up interval ranged from 12 to 36 months (mean 17 months, median 15 months). The success rate was 51/58 (87.9%) in all 58 EDCRs. The success rate was 47/51 (92.2%) in the group of postsaccal obstructions, 3/5 (60.0%) in the group of postsaccal and suprasaccal obstrutcions and 1/2 (50.0%) in presaccal obstructions. The procedures were successful in all eight children aged under 1 year old (100%) and in 14 of 15 children between 1 and 2 years old (93.3%). The silicone intubation was used in 54 EDCRs. CONCLUSIONS: The endoscopic DCR is a safe and effective procedure for most children with the success rate comparable to that achieved in the external DCR and in adults. The success rate of the postsaccal obstructions is significantly higher than in presaccal or combined pre- and postsaccal obstructions.
Keywords: Child; Nasal Cavity; nosní dutina; Female; předškolní dítě; dakryocystorinostomie; endoskopie; Humans; ženské pohlaví; Infant; mužské pohlaví; Male; lidé; Child, Preschool; kojenec; dítě; Endoscopy; Dacryocystorhinostomy